2009
DOI: 10.1038/modpathol.2008.184
|View full text |Cite
|
Sign up to set email alerts
|

Secretory breast carcinomas with ETV6-NTRK3 fusion gene belong to the basal-like carcinoma spectrum

Abstract: Secretory breast carcinomas (o0.15% of breast tumors) are associated with a characteristic morphology and a favorable prognosis. Remarkably, this entity is the only epithelial tumor of the breast with a balanced translocation, t(12;15), that creates an ETV6-NTRK3 gene fusion encoding chimeric tyrosine kinase also encountered in cellular mesoblastic nephroma and infantile fibrosarcoma. The aim of this study was to determine the phenotypic class (ie luminal A/B, ERBB2, basal-like) of secretory breast carcinoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(85 citation statements)
references
References 21 publications
2
82
1
Order By: Relevance
“…prognosis. 7 This view is confirmed by our present study. However, the clinical significance of this finding is not clear at this time.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…prognosis. 7 This view is confirmed by our present study. However, the clinical significance of this finding is not clear at this time.…”
Section: Discussionsupporting
confidence: 82%
“…7 In this retrospective study, 15 cases of secretory breast carcinoma were retrieved from a series of 10 000 newly diagnosed breast cancers between 2006 and 2010, with an incidence of only 0.15%. The reported male-female ratio is approximately 1:6, 9 which is similar to the distribution in our data set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These neoplasms can have late local recurrences but is generally associated with prolonged survival, even with axillary lymphnode involvement [3,4]. Immunochemically, the tumor usually shows strong reactivity for S-100 but is negative for estrogen receptor (ER), progesterone receptor (PR) and HER2 neu protein [5][6][7]. In 2002, Tognon et al [8] reported that secretory breast carcinoma expressed the ETV6-NTRK3 gene fusion in 12 out of 13 of their cases, which is now considered to be a differentiating factor from other basal-like breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs more often in younger women than in elderly women (3). Molecularly, mammary SC is the only epithelial tumor with the t(12;15)(p13;q25) translocation in breast, leading to a fusion of the ETV6 gene from chromosome 12 and the NTRK3 gene from chromosome 15 (4,5). The ETV6-NTRK3 fusion gene encodes a chimeric tyrosine kinase, and this fusion results in a constitutively active chimeric tyrosine kinase mitogenic pathway and the phosphatidyl inositol-3-kinase (PI3K)-AKT pathway (6,7).…”
Section: Introductionmentioning
confidence: 99%